2021
DOI: 10.1038/s41598-021-95261-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-screening for osteoporosis with calcaneus quantitative ultrasound and dual-energy X-ray absorptiometry bone density

Abstract: Calcaneal quantitative ultrasonography (QUS) is a useful prescreening tool for osteoporosis, while the dual-energy X-ray absorptiometry (DXA) is the mainstream in clinical practice. We evaluated the correlation between QUS and DXA in a Taiwanese population. A total of 772 patients were enrolled and demographic data were recorded with the QUS and DXA T-score over the hip and spine. The correlation coefficient of QUS with the DXA-hip was 0.171. For DXA-spine, it was 0.135 overall, 0.237 in females, and 0.255 in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Calcaneal quantitative ultrasound is an alternative approach to assess bone health, which was suggested for pre-screening and risk evaluation for osteoporosis (Gao et al, 2021 ; Yen et al, 2021 ). Notwithstanding, Frost et al ( 2001 ) found that the precision of calcaneal quantitative ultrasound was not good enough to be used for monitoring response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Calcaneal quantitative ultrasound is an alternative approach to assess bone health, which was suggested for pre-screening and risk evaluation for osteoporosis (Gao et al, 2021 ; Yen et al, 2021 ). Notwithstanding, Frost et al ( 2001 ) found that the precision of calcaneal quantitative ultrasound was not good enough to be used for monitoring response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The performance (sensitivity, specificity, accuracy, positive predictive value, and negative predictive value) of the SVM models and PCA models in the test dataset were evaluated and compared to the univariate models using the CT attenuation of the calcaneus and medial cuneiform using DeLong's test. The calcaneus has been historically used as the bone evaluated in the foot and ankle for screening for osteoporosis [ 18 , 19 ]. In addition, a recent study showed that the distal dorsal lateral aspect of medial cuneiform had higher CT attenuation and was denser than all other sites in the medial cuneiform and suggested that this site should be used for hardware implantation [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…More recent data has shown that opportunistic screening for osteoporosis and osteopenia can be accomplished using the computed tomography (CT) attenuation of the lumbar and thoracic spine from CT scans of the chest, abdomen, and pelvis [ 16 , 17 ]. BMD measurements are sometimes obtained using quantitative ultrasound at the calcaneus [ 18 , 19 ]. Because the quantitative ultrasound BMD measurements at the calcaneus can be used to predict osteoporotic fractures, we hypothesized that the CT attenuation of the calcaneus would be correlated with DXA BMD measurements.…”
Section: Introductionmentioning
confidence: 99%
“…2 Drug cargo is released, and acoustically powered drug delivery is provided. 3 Intracellular reactive oxygen species (ROS) may also be involved in cytotoxicity due to ultrasound excitation and generation. ROS-mediated mitochondrial membrane damage and the release of cytochrome c induce apoptosis.…”
Section: Ultrasonic Diagnosismentioning
confidence: 99%
“…Generally, preliminary testing is accomplished via collection (e.g., blood, urine) and other noninvasive methods [1,2]. It is usually possible to visualize deep tissue through contrast imaging methods such as X-rays [3], computed tomography (CT) [4], magnetic resonance imaging (MRI) [5], positron emission tomography (PET) scan [6], radionuclide scan, or ultrasound [7]. To visualize these images, contrast agents are injected into the tissue.…”
Section: Introductionmentioning
confidence: 99%